La reprise du motif symboliste du faune dans L'Ange de Dominique d'Anne Hébert - Mottet, Philippe (Romanica Silesiana)
The article explores rewriting strategies in Anne Herbert’s work, focusing on ‘L’Ange de Dominique’, the story which explicitly refers to the aesthetics, style and imagination of the French Symbolists (Rimbaud, Mallarmé, Debussy and Nijinsky) through the character of the faun. Herbert’s novella is interpreted as a portrayal of the sensibility and poetry at the turn of the century. Key words: Anne Herbert; Le Torrent; literature of the fin de siècle; Quebec; rewriting; faun; Symbolism; novella